2013
DOI: 10.1001/jamaoto.2013.5054
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of Elderly Patients After Head and Neck Reconstruction

Abstract: Elderly patients are less likely to be discharged home after free flap reconstruction. Age, ASA score, and length of stay are independent factors for discharge to a nursing or other care facility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
52
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(61 citation statements)
references
References 37 publications
8
52
0
1
Order By: Relevance
“…Graboyes et al also found LOS to be a dependent risk factor for 30dUR in otolaryngology patients. LOS ≥5 days likely represents a group of complex patients or with more comorbid conditions . Moreover, it reflects increased opportunity for hospital‐acquired complications, such as infections and deconditioning to occur …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graboyes et al also found LOS to be a dependent risk factor for 30dUR in otolaryngology patients. LOS ≥5 days likely represents a group of complex patients or with more comorbid conditions . Moreover, it reflects increased opportunity for hospital‐acquired complications, such as infections and deconditioning to occur …”
Section: Discussionmentioning
confidence: 99%
“…LOS 5 days likely represents a group of complex patients or with more comorbid conditions. [27][28][29] Moreover, it reflects increased opportunity for hospital-acquired complications, such as infections and deconditioning to occur. 29,30 G-tube presence at discharge predicted postoperative 30dUR (p 5 .01).…”
Section: Predictors Of Readmissionmentioning
confidence: 99%
“…oral cavity versus pharynx) or flap selection and hospital disposition. 20 Improvements in medical management, anaesthesia, and reconstructive surgery have allowed the successful treatment of elderly patients with head and neck cancers. Appropriate treatment should be based on individual patient desires and physical tolerance to surgery/treatment rather than based on age as the ultimate deciding factor.…”
Section: Discussionmentioning
confidence: 99%
“…However, head and neck cancer patients often carry multiple medical and social comorbidities, increasing their risk for suboptimal outcomes . They require complex coordination of care including tracheostomy and enteral feeding tube care, rehabilitation, discharge planning, and wound care …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] They require complex coordination of care including tracheostomy and enteral feeding tube care, rehabilitation, discharge planning, and wound care. 3,11,12 Otolaryngology-head and neck surgery residency training programs function with rotating resident physicians. Residents are spread between inpatient care, outpatient clinics, and operating rooms.…”
Section: Introductionmentioning
confidence: 99%